2011
DOI: 10.1097/mbc.0b013e328342791b
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function alterations and their relation to P-selectin (CD62P) expression in children with iron deficiency anemia

Abstract: Iron deficiency anemia (IDA) may cause platelet aggregation dysfunction and this can be reversed by iron therapy. On the other hand, it has been reported that the platelet fractions carrying the platelet activation markers, CD62P and CD63, are increased in thalassemic patients and there is a significant correlation between the increased levels of soluble P-selectin and free iron in sickle cell disease. This study was performed to investigate the alterations of platelet functions and whether iron deficiency res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…Our group has previously shown that baseline and ADP-stimulated platelet P-selectin expression was higher in IBD patients with ID as compared to after iron replacement therapy 19 . In another study on children with IDA, P-selectin was likewise elevated on agonist stimulation 34 . Apart from platelet P-selectin, we also found in the current study that plasma soluble P-selectin was increased in ID and diminished upon iron replacement therapy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our group has previously shown that baseline and ADP-stimulated platelet P-selectin expression was higher in IBD patients with ID as compared to after iron replacement therapy 19 . In another study on children with IDA, P-selectin was likewise elevated on agonist stimulation 34 . Apart from platelet P-selectin, we also found in the current study that plasma soluble P-selectin was increased in ID and diminished upon iron replacement therapy.…”
Section: Discussionmentioning
confidence: 85%
“…We did not find a significant difference in platelet aggregability to ADP or collagen in ID, although our previous study showed increased aggregability to ADP in platelets from rats after 2 weeks on ID, which then diminished by 3 weeks 16 . Several patient studies have actually reported impaired aggregability to ADP or collagen in IDA 34 , which increases with iron replacement therapy [38][39][40] . This occurred despite an increased PLT in ID in some studies 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of severe maternal IDA on neonatal platelet indices has not been studied so far. Several authors have demonstrated platelet aggregation and adhesion dysfunction and its reversal after iron therapy in children with IDA [9,10]. Perlman et al have demonstrated an association between severe IDA and thrombocytopenia in children of age 14 mo to 17 y.…”
Section: Discussionmentioning
confidence: 96%
“…However, there is paucity of literature regarding the effect of maternal iron deficiency and low fetal iron store on fetal thrombopoiesis. Several studies in children or older age group have found a relationship between iron metabolism and thrombopoiesis with iron deficiency anemia (IDA), either in the form of abnormal platelet counts [7,8], or abnormal platelet function [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the relationships between with iron and platelet function were shown in many studies [20,21] . Yıldırım et al [20] reported that platelet aggregation and adhesion have been delayed in children with iron deficiency anemia. Pratićo et al [21] found that iron (Fe 2+ )…”
Section: Study Limitationsmentioning
confidence: 97%